Care of the patient with an autism spectrum disorder by the general physician. Issue 1042 (16th March 2012) - Venkat, Arvind; Jauch, Edward; Russell, William Scott; Crist, Candace Roman; Farrell, Robert
Abstract : Autism spectrum disorders (ASD), comprising classic autism, Asperger syndrome, Rett syndrome, childhood disintegrative disorder and pervasive development disorder-not otherwise specified, represent complex neurodevelopmental conditions characterised by impaired social interactions, difficulties with communication and repetitive, stereotyped behaviours. It is estimated that up to 1% of the general population may be affected by an ASD. Whether due to improved diagnostic techniques or a true rise in incidence, the prevalence of patients with ASD is rising, and these individuals are increasingly encountered in a variety of healthcare settings. Care givers of patients with an ASD report frequently that lack of awareness of the complications of these disorders and the method of appropriately assessing these individuals impair the effective delivery of healthcare to this patient population. It is now clear that patients with an ASD, in addition to the defining characteristics of these disorders, can present to the outpatient, emergency department and inpatient settings with a variety of psychiatric, neurological, gastrointestinal, nutritional/metabolic, dental, ophthalmological, cardiovascular, gynaecological, traumatic and musculoskeletal conditions that can require acute intervention. In addition, the common treatments given to patients with an ASD may result in side effects and complications that may require acute intervention. For physicians who encounter patients with an ASD, the combination of impaired social interactions, difficulties with communication and stereotyped behaviours creates an additional barrier to diagnosis and treatment of these individuals. Careful preparation of the examination environment, direct engagement of care givers and the patient and the use of communication techniques and pharmacological adjuncts can aid physicians in treating the patient with an ASD in the outpatient, emergency department and inpatient settings.